The Concept of Originality and Creativity in the Humanities, the Social Sciences and the Natural Sciences - Sta. Maria, Madelene (Animo Repository, 2022)
The study was conducted to determine how 21 experts in the discipline clusters of humanities, the social sciences and the natural sciences defined originality and creativity in terms of how these concepts are understood and realized in the production of works in their respective disciplines, what related copyright issues emerge related to these concepts, and how these two concepts are related. Through thematic qualitative analysis of in-depth interview data, findings suggest that while there may be converging ideas about originality and creativity among the discipline clusters, the way this concept is operationalized by each discipline significantly vary. The study is deemed useful because apart from clarifying vague notions about original works, the study can serve as reference for legislators in amending the Copyright law, and for law practitioners in contextualizing cases involving original and derivative works, plagiarism and other related concepts. In this connection, the study provides the implications for the evaluation of the originality and creativity in works produced from the various discipline clusters.